Avaliação e calibração de extratores de fósforo disponível em solos da zona abacaxicultora paraibana. - Silva, Mateus Guimarães da (2018)
The establishment of P rates for pineapple in the state of Paraíba are based from the Mehlich- 1 extractor. However, considering changes in the production system, the lack of information on the calibration tests, that Mehlich-1 extractor presents different capacities to dissolve and solubilize the P in phosphate compounds, and the interest in the adoption of multielementary extractors it becomes important to evaluate the adequacy of existing information, as well as to test the efficiency of other chemical extractors. Thus, the objective of this work was to evaluate the performance of the Mehlich-1 (M-1), Mehlich-3 (M-3), Ion Exchange Resin (RTI) and Bray-1 (B-1) extractors in the evaluation of available P in soils of the Paraiba pineapple zone; establish classes of interpretation of levels and rates of P2O5 to be recommended, according to the availability of P evaluated by the tested extractors. The experiments were carried out with 'Pérola' pineapple, under edaphoclimatic conditions representative of the Paraiba pineapple zone. Two soils were used: Plinthic Dystrophic Red- Yellow Argissolo (PVAdp), from the municipality of Itapororoca, and Argissolo endoeutrófico Amarelo (PAea) from the municipality of Sapé. The treatments consisted of six doses of P (0, 20, 120, 200, 280 and 380 kg ha-1 of P2O5 in PVAdp and 0, 8, 48, 80, 112 and 152 kg ha-1 of P2O5 in PAea) applied in the third month after planting. The experimental design was in randomized blocks, with three replications, and 18 experimental units. In the soil samples collected 90 days after harvesting, the levels of P available by extractors M-1, M- 3, RTI and B-1 were determined. In the ‘D’ leaf samples collected at floral induction period, the content and accumulation of P were determined. The amounts extracted and the rates of P recovery varied between soils and extractors. The PVAdp soil extracted less, but had a higher P recovery rate than PAea; M-3 and RTI had the highest values, B-1 the lowest, with M-1 having intermediate values for these characteristics. The availability of P can be assessed in both soils by any of the tested extractors; their performance is similar in PAea and better for extractors B-1 and M-1 in PVAdp. The critical levels of P, determined by the extractors M-1, M-3, RTI and B-1, were 32.5; 58.5; 38.0 and 29.5 mg dm-3 , respectively. The MEF doses were 296.5 and 110.5 kg ha-1 of P2O5, respectively, for the PVAdp and PAea soils, while the MEE doses were, respectively, 91.5 and 53.0 kg ha-1 of P2O5. 16 The availability of P in the evaluated soils can be stratified into three fertility classes (low, medium and high), depending on the extractor. For low, medium and high fertility classes are recommended doses of 160.0; 80.0 and 20.0 kg ha-1 of P2O5 when the availability assessment is made by the M-1 extractor, and 150.0; 75.0 and 20.0 kg ha-1 of P2O5 for evaluation with the RTI extractor.